Battery and electronic equipment

CN119547242APending Publication Date: 2025-02-28ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380014342.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing semi-solid and solid-state lithium-ion batteries have insufficient thermal stability at high temperatures, resulting in poor safety and circulation performance, making it difficult to meet the demand for high energy density and long battery life in the new energy field.

Method used

Using an electrolyte with high thermal stability, the thermogravimetric analysis is performed under a nitrogen atmosphere to ensure that the weight loss rate of the electrolyte between 100°C and 600°C is 3 to 85%, and the pretreatment, curing and shaping treatment are performed. The battery is prepared to form an electrolyte with good thermal stability.

Benefits of technology

It effectively extends the ARC thermal runaway time of the battery, improves the safety and circulation performance of the battery, and improves the discharge performance of the battery at different temperatures and magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547242A_ABST
    Figure CN119547242A_ABST
Patent Text Reader

Abstract

The invention provides a battery and electronic equipment. A first aspect of the present application provides a battery comprising an electrolyte; in a nitrogen atmosphere, the electrolyte is subjected to thermogravimetric analysis at a heating speed of 5 DEG C / min, and the electrolyte has at least one weight loss peak between 100 DEG C and 600 DEG C. The battery provided by the invention has relatively good thermal stability, the ARC thermal runaway time of the battery can be effectively prolonged, and the safety and cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Battery and electronic device Technical Field

[0001] The present application belongs to the field of batteries and relates to a battery and an electronic device. Background Art

[0002] With the rapid development of new energy, lithium-ion batteries are in urgent need of high energy density and superior safety. Compared to traditional liquid batteries, high-energy-density batteries offer higher energy density and longer battery life, and hold broader application prospects in cutting-edge consumer electronics, electric vehicles, energy storage devices, and other new energy sectors.

[0003] Semi-solid batteries, or solid-state batteries, are an iterative product in the transition toward high-energy-density batteries. Like liquid batteries, they contain positive and negative electrodes and a separator. The difference lies in the use of semi-solid electrolytes, while solid-state batteries use solid electrolytes and liquid batteries use liquid electrolytes. Compared to liquid batteries, semi-solid batteries or solid-state batteries require greater thermal stability. Therefore, improving the safety of semi-solid or solid-state batteries is a hot topic of ongoing research in this field.

[0004] Summary of the Invention

[0005] The present application provides a battery, including an electrolyte. The electrolyte has good thermal stability, which helps to prolong the ARC thermal runaway time of the battery and improve the safety of the battery.

[0006] The present application also provides an electronic device comprising the above-mentioned battery.

[0007] The present application provides a battery, comprising an electrolyte;

[0008] In a nitrogen atmosphere, a thermogravimetric analysis is performed on the electrolyte at a heating rate of 5° C. / min. The electrolyte has at least one weight loss peak between 100° C. and 600° C.

[0009] In the battery as described above, the weight loss rate of the electrolyte at 100° C. to 600° C. is 3 to 85%.

[0010] The battery as described above is subjected to thermogravimetric analysis of the electrolyte in a nitrogen atmosphere, starting from an initial temperature T0 at a heating rate of 5°C / min, where the initial temperature T0 is 25°C and the mass of the electrolyte at the initial temperature T0 is M0;

[0011] The electrolyte satisfies at least one of the following:

[0012] (1) When the temperature T reaches 100°C, the mass of the electrolyte is ≥96.13%*M0;

[0013] (2) When the temperature T reaches 200°C, the mass of the electrolyte is ≥49.46%*M0;

[0014] (3) When the temperature T reaches 300°C, the mass of the electrolyte is ≥35.02%*M0;

[0015] (4) When the temperature T reaches 400°C, the mass of the electrolyte is ≥ 27.51%*M0;

[0016] (5) When the temperature T reaches 500°C, the mass of the electrolyte is ≥19.06%*M0;

[0017] (6) When the temperature T reaches 590℃, the mass of the electrolyte is ≥17.74%*M0.

[0018] The battery as described above, wherein the electrolyte has M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y in an X-ray diffraction pattern, M ≥ 1, N ≥ 1;

[0019] Among them, 10°≤x≤30°, 30°≤y≤50°;

[0020] The sum of the half-peak widths of the M first diffraction peaks is a, and the sum of the half-peak widths of the N second diffraction peaks is b, wherein 1.2≤b / a≤3.0.

[0021] For the battery as described above, 1.7≤b / a≤2.2;

[0022] Or, 2.7≤b / a≤2.95.

[0023] For the battery as described above, 0.8≤a≤1.4, and 1.2≤b≤3.5.

[0024] The battery as described above is a solid-state battery or a semi-solid-state battery.

[0025] In the battery as described above, the electrolyte is a solid electrolyte or a semi-solid electrolyte.

[0026] In the battery as described above, the electrolyte includes a polymer obtained by polymerizing a monomer, the monomer includes a functional group, and the functional group includes at least two acrylate groups.

[0027] In the battery as described above, the polymerized monomer includes one or more of a bifunctional monomer, a trifunctional monomer, a tetrafunctional monomer, and a hexafunctional monomer.

[0028] In the battery as described above, the bifunctional monomer includes one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, and ethoxylated bisphenol A diacrylate and its derivatives;

[0029] And / or, the trifunctional monomer includes one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives;

[0030] and / or, the tetrafunctional monomer comprises ethoxylated (5) pentaerythritol tetraacrylate and its derivatives;

[0031] And / or, the hexafunctional monomer includes dipentaerythritol hexaacrylate and its derivatives.

[0032] The battery as described above is prepared by a method comprising the following steps:

[0033] sequentially performing a pretreatment, a curing and formation treatment, and a formation treatment on a battery comprising an electrolyte precursor solution to obtain the battery, wherein the electrolyte precursor solution comprises a polymerizable monomer;

[0034] The pretreatment comprises: subjecting the electrolyte precursor solution including the polymerizable monomer to a prepolymerization reaction at 40° C. to 60° C. for 0.5 h to 2 h;

[0035] The curing treatment comprises: charging the pretreated battery to 3.7V at a temperature of 60°C to 80°C, a pressure of ≤3MPa, and a rate of ≤0.3C;

[0036] The chemical formation treatment comprises: charging the battery after the curing chemical formation treatment to a cut-off voltage of ≥4.0V at a temperature of 60°C to 90°C, a pressure of ≤3MPa, and a rate of ≤1C to obtain the battery.

[0037] In the battery as described above, the electrolyte comprises 0.05 wt% to 9 wt% of a polymer and 91 wt% to 99.5 wt% of an electrolyte solution.

[0038] In the battery as described above, the electrolyte includes a lithium salt and a non-aqueous organic solvent.

[0039] In the battery as described above, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide and lithium bistrifluoromethylsulfonyl imide.

[0040] In the battery as described above, the non-aqueous organic solvent is selected from one or more of cyclic carbonates, linear carbonates, and linear carboxylates.

[0041] The battery as described above also includes a positive electrode sheet; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material, lithium nickel cobalt oxide, lithium nickel titanium magnesium oxide, lithium nickel oxide, spinel lithium manganese oxide, nickel cobalt tungsten, lithium nickel manganese oxide, and sodium-containing lithium cobalt oxide.

[0042] The battery as described above also includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of silicon, silicon carbon, SiOx, lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives, aluminum and its derivatives, magnesium and its derivatives, bismuth and its derivatives, nickel and its derivatives, silver and its derivatives, zinc and its derivatives, titanium and its derivatives, gallium and its derivatives, indium and its derivatives, tin and its derivatives, lithium nitride, and copper nitride.

[0043] A second aspect of the present application provides an electronic device comprising any of the above-mentioned batteries.

[0044] The battery provided in the present application includes an electrolyte, which has a low weight loss rate as the temperature increases, indicating that the electrolyte has good thermal stability, can effectively prolong the ARC thermal runaway time of the battery, and improve the safety and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] FIG1 is a thermogravimetric analysis result of the electrolyte provided in Example 1 of the present application;

[0046] FIG2 is a thermogravimetric analysis result of the electrolyte provided in Example 4 of the present application;

[0047] FIG3 is a thermogravimetric analysis result of the electrolyte provided in Example 5 of the present application;

[0048] FIG4 is a thermal runaway analysis result of the battery provided in Example 1 of the present application;

[0049] FIG5 is a thermal runaway analysis result of a battery provided in Example 2 of the present application;

[0050] FIG6 is a thermal runaway analysis result of a battery provided in Example 3 of the present application;

[0051] [Corrected 18.07.2023 according to Rule 26] FIG7 shows the thermal runaway analysis results of the battery provided in Example 4 of the present application;

[0052] [Corrected 18.07.2023 according to Rule 26] Figure 8 shows the thermal runaway analysis results of the battery provided in Comparative Example 1 of this application; [0052.1][Corrected 18.07.2023 according to Rule 26] Figure 9 shows the thermal runaway analysis results of the battery provided in Comparative Example 2 of this application. DETAILED DESCRIPTION

[0053] To make the purpose, technical solutions, and advantages of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0054] The present application provides a battery, comprising an electrolyte;

[0055] In a nitrogen atmosphere, a thermogravimetric analysis is performed on the electrolyte at a heating rate of 5° C. / min. The electrolyte has at least one weight loss peak between 100° C. and 600° C.

[0056] Furthermore, the weight loss rate of the electrolyte at 100° C. to 600° C. is 3 to 85%.

[0057] Furthermore, a thermogravimetric analysis of the electrolyte is performed under a nitrogen atmosphere, starting from an initial temperature T0 at a heating rate of 5°C / min, where the initial temperature T0 is 25°C and the mass of the electrolyte at the initial temperature T0 is M0;

[0058] The electrolyte satisfies at least one of the following:

[0059] (1) When the temperature T reaches 100°C, the mass of the electrolyte is ≥96.13%*M0;

[0060] (2) When the temperature T reaches 200°C, the mass of the electrolyte is ≥49.46%*M0;

[0061] (3) When the temperature T reaches 300°C, the mass of the electrolyte is ≥35.02%*M0;

[0062] (4) When the temperature T reaches 400°C, the mass of the electrolyte is ≥ 27.51%*M0;

[0063] (5) When the temperature T reaches 500°C, the mass of the electrolyte is ≥19.06%*M0;

[0064] (6) When the temperature T reaches 590℃, the mass of the electrolyte is ≥17.74%*M0.

[0065] The battery provided in the present application includes an electrolyte, which has a lower weight loss rate as the temperature increases, indicating good thermal stability.

[0066] It should be noted that when performing thermogravimetric analysis on electrolytes, the electrolytes must be pretreated to remove impurities. In particular, when analyzing the electrolyte in a battery, the battery must be disassembled, the electrolyte rinsed with deionized water, and the solid phase collected. After drying at 100°C for 24 hours, the solid phase was subjected to thermogravimetric analysis. Thermogravimetric analysis is performed using a thermogravimeter.

[0067] During the thermogravimetric analysis process, the mass M0 of the electrolyte was tested at an initial temperature T0 of 25°C. The temperature was then raised at a rate of 5°C / min, and the mass of the electrolyte was tested at different temperatures. As the temperature continued to rise, the mass of the electrolyte continued to decrease, but the loss of the electrolyte provided by this application was able to be kept within a small range, indicating that the electrolyte provided by this application has good thermal stability, can effectively prolong the battery's ARC thermal runaway time, and improve the battery's safety and cycle performance.

[0068] In a specific embodiment, the X-ray diffraction pattern of the electrolyte has M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y, M≥1, N≥1; wherein, 10°≤x≤30°, 30°≤y≤50°; the sum of the half-peak widths of the M first diffraction peaks is a, and the sum of the half-peak widths of the N second diffraction peaks is b, wherein, 1.2≤b / a≤3.0.

[0069] When the electrolyte meets the above requirements, it indicates that the electrolyte has special crystallization properties, which is conducive to the conduction of lithium ions in the electrolyte, so that the electrolyte has good electrical conductivity, and then the battery including the electrolyte has good discharge performance at different rates and different temperatures, showing excellent rate performance and temperature characteristics, especially more advantageous in discharging at high rates and low temperatures.

[0070] Further, 1.7≤b / a≤2.2; or, 2.7≤b / a≤2.95.

[0071] Furthermore, 0.8≤a≤1.4, 1.2≤b≤3.5.

[0072] It's important to note that when performing X-ray diffraction analysis on electrolytes, especially those in batteries, the electrolytes must be pretreated after disassembly to remove other components. This pretreatment involves washing the electrolyte with deionized water, vacuuming it at 80°C for 48 hours, and testing for a moisture content of less than 1000 ppm before performing X-ray diffraction analysis.

[0073] In a specific embodiment, the electrolyte includes a polymer obtained by polymerizing a polymerized monomer, wherein the polymerized monomer includes a functional group, and the functional group includes at least two acrylate groups.

[0074] Furthermore, the polymerizable monomer is selected from one or more of a difunctional monomer, a trifunctional monomer, a tetrafunctional monomer, and a hexafunctional monomer.

[0075] Specifically, the difunctional monomer refers to a polymer monomer containing two carbon-carbon double bonds, including but not limited to one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, and ethoxylated bisphenol A diacrylate and its derivatives.

[0076] The trifunctional monomer refers to a polymer monomer containing three carbon-carbon double bonds, including but not limited to one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, and trimethylolpropane trimethacrylate and its derivatives.

[0077] The tetrafunctional monomer is ethoxylated (5) pentaerythritol tetraacrylate and its derivatives;

[0078] The hexafunctional monomer is dipentaerythritol hexaacrylate and its derivatives.

[0079] It should be noted that the above-mentioned derivatives refer to products obtained by replacing the original groups in the main body with new substituent groups. For example, the derivatives of ethoxylated trimethylolpropane triacrylate refer to products obtained by replacing the original groups (e.g., hydrogen atoms) in ethoxylated trimethylolpropane triacrylate with substituent groups. The present invention is not limited to the specific choice of substituent groups, and for example, the substituent groups can be at least one of halogen atoms, hydroxyl groups, thiol groups, nitro groups, cyano groups, isocyano groups, sulfone groups, hydroxylamine groups, carboxyl groups, carbonyl groups, aromatic hydrocarbons, heteroaromatic hydrocarbons, heterocycloalkyl groups, amino groups, alkoxy groups, aromatic ring oxygen groups, aromatic heterocyclooxy groups, amide groups, alkylthio groups, aromatic ring sulfur groups, heteroaromatic ring sulfur groups, silicon groups, boron groups, etc.

[0080] Furthermore, the battery is prepared by a method comprising the following steps:

[0081] sequentially performing a pretreatment, a curing and formation treatment, and a formation treatment on a battery comprising an electrolyte precursor solution to obtain the battery, wherein the electrolyte precursor solution comprises the polymerized monomer;

[0082] The pretreatment comprises: subjecting the electrolyte precursor solution including the polymerizable monomer to a prepolymerization reaction at 40° C. to 60° C. for 0.5 h to 2 h;

[0083] The curing treatment comprises: charging the pre-treated battery to 3.7V at a temperature of 60°C to 80°C, a pressure of ≤3MPa, and a rate of ≤0.3C;

[0084] The chemical formation treatment comprises: charging the battery after the curing chemical formation treatment to a cut-off voltage of ≥4.0V at a temperature of 60°C to 90°C, a pressure of ≤3MPa, and a rate of ≤1C to obtain the battery.

[0085] The present application helps to obtain an electrolyte with good thermal stability through pretreatment-curing and formation treatment-formation treatment. The polymerized monomer has a reactive group. During the pretreatment process, a polymerization and curing reaction can be carried out to form a preliminary electrolyte skeleton structure; then, during the curing and formation treatment process, the polymerized monomer is further cured to form an electrolyte and remove the unreacted polymerized monomer, and a formation treatment is carried out at the same time, which helps to form a thermally stable electrolyte inside the battery. Subsequently, a formation treatment is carried out to obtain an electrolyte. The method provided by the present invention helps to improve the thermal stability of the electrolyte, prolong the ARC thermal runaway time of the battery, and make the battery have higher safety performance.

[0086] It is understood that the electrolyte precursor solution also includes an initiator for initiating the polymerization of the polymerization monomer. Specifically, the initiator includes but is not limited to one or more of benzoyl peroxide, tert-butyl benzoyl peroxide, lauroyl peroxide, tert-butyl benzoyl peroxide, azobisisobutyronitrile, tert-butyl peroxyvalerate, and tert-butyl perbenzoate.

[0087] In a specific embodiment, the battery is a semi-solid battery, and the electrolyte comprises 0.05 wt% to 9 wt% of a polymer and 91 wt% to 99.5 wt% of an electrolyte.

[0088] It can be understood that when the battery is a semi-solid-state battery, the electrolyte precursor solution also includes components required for the electrolyte. Specifically, the electrolyte includes a lithium salt and a non-aqueous organic solvent.

[0089] The lithium salt can be selected from the lithium salts of electrolytes commonly used in the art, including but not limited to one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium difluorobis(oxalato)phosphate, lithium tetrafluoro(oxalato)phosphate, lithium difluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0090] In a specific embodiment, the non-aqueous organic solvent is selected from one or more of cyclic carbonates, linear carbonates, and linear carboxylic esters.

[0091] Among them, the cyclic carbonate is selected from one or more of ethylene carbonate and propylene carbonate, the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate, and the linear carboxylic ester is selected from one or more of ethyl propionate, propyl propionate, and propyl acetate.

[0092] In a specific embodiment, the mass content of the cyclic carbonate in the non-aqueous organic solvent is 20 - 60 wt%, and the mass content of the linear carbonate and / or linear carboxylic ester is 40 - 80 wt%.

[0093] In addition, the lithium salt electrolyte further includes additives, and the additives can be added according to the conventional technical means in the art to improve the comprehensive performance of the battery. For example, the additives are selected from one or more of vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, ethylene sulfate, 1,3 - propylene sulfonic acid lactone, lithium difluorophosphate, lithium bis(oxalato)borate, organic phosphides, organic fluorides, and fluorinated alkyl phosphates.

[0094] In addition, in the battery of the present application, in addition to the electrolyte, it further includes a positive electrode sheet, a negative electrode sheet, and a separator.

[0095] Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer provided on the surface of the positive electrode current collector. The material of the positive electrode sheet can be a conventional material in the art. For example, the positive electrode current collector can be a conventional metal foil such as aluminum foil; the positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder, and an additive.

[0096] Among them, the positive electrode active material can be selected from lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (Li y , 1-x-y , z , x , y , 1-x-y , z , x Ni x Co y Mn 1-x-y O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, 0 < x + y < 1), lithium manganese oxide (LiMnO2), lithium nickel cobalt aluminum oxide (Li z Ni x Co y Al<O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, 0.8 ≤ x + y < 1), lithium nickel cobalt manganese aluminate (Li z Ni x Co y Mn w Al 1-x-y-w O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, w > 0, 0.8 ≤ x + y + w < 1), nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution cathode material (xLi2MnO3·(1 - x)LiMO2, where M = Ni / Co / Mn), lithium nickel cobalt oxide (LiNi x Co y O2, where x > 0, y > 0, x + y = 1), lithium nickel titanium magnesium oxide (LiNi x Ti y Mg z O2, where, x > 0, y > 0, z > 0, x + y + z = 1), lithium nickel oxide (Li2NiO2), spinel lithium manganate (LiMn2O4), nickel cobalt tungsten, lithium nickel manganate, sodium-containing cobalt oxide (Lin 1-y1 Na y1 Co 1-a1-b1 M1 b1 M2 a1 O2 or Li n2-y2-b2 Na y2 Co 1-a2 M1 b2 M 2a 2O2, 0.6 ≤ n1 ≤ 0.8, 0 < y1 ≤ 0.05, 0 ≤ a1 ≤ 0.1, 0 < b1 ≤ 0.1, 0 < b1 / (1 - a1 - b1) < 0.1; 0.6 ≤ n2 ≤ 0.8, 0 < y2 ≤ 0.05, 0 ≤ a2 ≤ 0.1, 0 < b2 ≤ 0.02; M1 is selected from at least one of Te, W, Al, B, P, and K; M2 is a doping element different from M1 such as Mg, Zr, Y, La, Ni, etc.) one or more of them.

[0097] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer provided on the surface of the negative electrode current collector. The negative electrode current collector can be selected from the negative electrode current collectors commonly used in the art, such as copper foil. The negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder, and an additive.

[0098] Among them, the negative electrode active material can be selected from at least one of silicon, silicon carbon, SiOx (0<X<2), lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives (such as boron powder, boron oxide), aluminum and its derivatives (such as aluminum powder, lithium aluminum alloy), magnesium and its derivatives (such as magnesium, magnesium aluminum alloy), bismuth and its derivatives (such as bismuth, lithium bismuth alloy), nickel and its derivatives (such as nickel, lithium nickel alloy, lithium nickel nitride), silver and its derivatives (such as silver powder, lithium silver alloy), zinc and its derivatives (such as zinc powder, zinc lithium alloy, zinc nitride), titanium and its derivatives (such as titanium powder, lithium titanate, titanium dioxide, lithium titanium alloy, etc.), gallium and its derivatives (such as gallium, lithium gallium alloy), indium and its derivatives (such as indium powder, lithium indium alloy), tin and its derivatives (such as tin powder, stannous oxide, tin oxide, tin sulfate), lithium nitride, and copper nitride.

[0099] The preparation method of the battery provided in this application can be prepared according to conventional methods in the art.

[0100] In a specific embodiment, first, positive and negative electrode sheets are prepared, wherein the preparation method of the positive electrode sheet comprises: mixing a positive electrode active material, a binder, a conductive agent, and an additive, adding a solvent (e.g., N-methylpyrrolidone), and stirring in a vacuum mixer until a positive electrode slurry with uniform fluidity is obtained, and then the positive electrode slurry is coated on one or both sides of a positive electrode current collector, and after drying at room temperature, the mixture is transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet. The preparation method of the negative electrode sheet comprises: mixing a negative electrode active material, a binder, a conductive agent, and an additive, adding a solvent (e.g., deionized water), and stirring in a vacuum mixer to obtain a negative electrode slurry, and then the negative electrode slurry is uniformly coated on one or both sides of a negative electrode current collector, and after drying at room temperature, the mixture is transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0101] The positive electrode sheet, separator and negative electrode sheet are stacked and assembled in sequence to obtain a battery cell, which is placed in an outer package, and an electrolyte precursor liquid is added. The battery is prepared after packaging, pretreatment, curing, formation and other processes.

[0102] The battery provided in this application will be described in detail below with reference to specific embodiments.

[0103] Example 1

[0104] The preparation method of the battery provided in this embodiment is as follows:

[0105] 1) Preparation of positive electrode

[0106] The positive electrode active material lithium nickel cobalt manganese oxide (nickel cobalt manganese 8:1:1), the binder polyvinylidene fluoride, the conductive agent carbon nanotubes and the conductive agent SP are mixed in a weight ratio of 96.5:2:0.5:1, N-methylpyrrolidone is added, and the mixture is stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is coated on both sides of an aluminum foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a positive electrode sheet.

[0107] 2) Preparation of negative electrode sheet

[0108] The negative electrode active material graphite, the negative electrode active material silicon carbon, the binder PAA, the binder SBR, the conductive agent CNT and the conductive agent SP are mixed in a weight ratio of 45:45:3:3:2:2, deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 35%; the negative electrode slurry is coated on both sides of the copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0109] 3) Preparation of electrolyte precursor solution

[0110] 3% ethylene glycol dimethacrylate, 2% triethylene glycol dimethacrylate, 0.05% benzoyl peroxide, 25% propylene carbonate (PC), 15% ethylene carbonate (EC), 15% diethyl carbonate (DEC), 25% ethyl methyl carbonate (EMC), 12.05% fluoroethylene carbonate (FEC), and 2.9% vinylene carbonate (VC) are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide (7:1) are added to the transparent liquid and dissolved to obtain a semi-electrolyte precursor solution with a lithium salt concentration of 1.45 mol / L.

[0111] 4) Battery assembly

[0112] The positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and assembled to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor solution is added, and a battery is prepared after packaging, pretreatment, curing and formation, and other processes;

[0113] The pretreatment includes: performing a prepolymerization reaction at a temperature of 60°C for 0.5h; subsequently, charging the pretreated battery to 3.7V at 0.3C at a temperature of 80°C and a pressure of 3MPa; and charging the cured battery to a cutoff voltage of 4.25V at a temperature of 80°C, a pressure of 3MPa, and a rate of 1C to obtain a battery.

[0114] Example 2

[0115] The battery provided in this embodiment can refer to Example 1, except that the electrolyte precursor solution has a different composition. The electrolyte precursor solution includes 5.4% ethylene glycol dimethacrylate, 3.6% triethylene glycol dimethacrylate, 0.09% benzoyl peroxide, 23.96% propylene carbonate (PC), 14.38% ethylene carbonate (EC), 14.38% diethyl carbonate (DEC), 23.96% methyl ethyl carbonate (EMC), 11.55% fluoroethylene carbonate (FEC), and 2.78% vinylene carbonate (VC). The mixture is uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide (7:1) are added to the transparent liquid and dissolved to obtain an electrolyte precursor solution having a lithium salt concentration of 1.45 mol / L.

[0116] Example 3

[0117] The battery provided in this embodiment can refer to Example 1, except that the difference lies in the difference between the curing and formation stages. The curing and formation stage information includes the following: the pretreatment comprises: performing a prepolymerization reaction at a temperature of 40°C for 2 hours; subsequently, charging the pretreated battery to 3.7V at 0.3C at a temperature of 80°C and a pressure of 3MPa; and charging the cured and formed battery to a cutoff voltage of 4.25V at a temperature of 80°C, a pressure of 0.1MPa, and a rate of 0.5C to obtain a battery.

[0118] Example 4

[0119] The preparation method of the battery provided in this embodiment is as follows:

[0120] 1) Preparation of positive electrode

[0121] Lithium nickel cobalt manganese oxide (nickel cobalt manganese 9:0.5:0.5), binder polyvinylidene fluoride, conductive agent carbon nanotubes and conductive agent SP are mixed in a weight ratio of 96.5:2:0.5:1, N-methylpyrrolidone is added, and the mixture is stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is coated on both sides of an aluminum foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a positive electrode sheet.

[0122] 2) Preparation of negative electrode sheet

[0123] The negative electrode active material graphite, the negative electrode active material silicon carbon, the binder PAA, the binder SBR, the conductive agent CNT and the conductive agent SP are mixed in a weight ratio of 80:10:3:3:2:2, deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 35%; the negative electrode slurry is coated on both sides of the copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0124] 3) Preparation of electrolyte precursor solution

[0125] 3% ethylene glycol dimethacrylate, 2% triethylene glycol dimethacrylate, 0.05% azobisisobutyronitrile, 25% propylene carbonate (PC), 15% ethylene carbonate (EC), 15% diethyl carbonate (DEC), 25% methyl ethyl carbonate (EMC), 12.05% fluoroethylene carbonate (FEC), and 2.9% vinylene carbonate (VC) are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bistrifluoromethylsulfonyl imide (7:1) are added to the transparent liquid and dissolved to obtain an electrolyte precursor solution with a lithium salt concentration of 1.45 mol / L.

[0126] 4) Battery assembly

[0127] The positive electrode sheet, the separator and the negative electrode sheet are stacked and assembled in sequence to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor solution is added, and the battery cell is prepared after packaging, pretreatment, curing and formation, and other processes.

[0128] Battery;

[0129] The pretreatment includes: performing a prepolymerization reaction at a temperature of 40°C for 2 hours; then, charging the pretreated battery to 3.7V at 0.3C under a temperature of 80°C and a pressure of 3MPa; and charging the cured battery to a cutoff voltage of 4.25V at a temperature of 90°C, a pressure of 0.1MPa, and a rate of 0.5C to obtain a battery.

[0130] Example 5

[0131] The preparation method of the battery provided in this embodiment is as follows:

[0132] 1) Preparation of positive electrode

[0133] Lithium cobalt oxide, binder polyvinylidene fluoride, conductive agent carbon nanotubes and conductive agent SP are mixed in a weight ratio of 96.5:2:0.5:1, N-methylpyrrolidone is added, and the mixture is stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is coated on both sides of an aluminum foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a positive electrode sheet.

[0134] 2) Preparation of negative electrode sheet

[0135] The negative electrode active material graphite, the negative electrode active material silicon carbon, the binder PAA, the binder SBR, the conductive agent CNT and the conductive agent SP are mixed in a weight ratio of 95:5:3:3:2:2, deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 35%; the negative electrode slurry is coated on both sides of the copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0136] 3) Preparation of electrolyte precursor solution

[0137] 2% tripropylene glycol diacrylate, 2% trimethylolpropane triacrylate, 0.04% tert-butyl peroxyvalerate, 25% propylene carbonate (PC), 15% ethylene carbonate (EC), 15% diethyl carbonate (DEC), 25% methyl ethyl carbonate (EMC), 13.06% fluoroethylene carbonate (FEC), and 2.9% vinylene carbonate (VC) are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide (10:1) are added to the transparent liquid and dissolved to obtain an electrolyte precursor solution with a lithium salt concentration of 1.45 mol / L.

[0138] 4) Battery assembly

[0139] The positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and assembled to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor solution is added, and a battery is prepared after packaging, pretreatment, curing and formation, and other processes;

[0140] The pretreatment includes: performing a prepolymerization reaction at a temperature of 50°C for 1 hour; subsequently, charging the pretreated battery to 4.1V at a temperature of 70°C and a pressure of 1MPa at 0.3C; and charging the cured battery to a cutoff voltage of 4.5V at a temperature of 85°C, a pressure of 0.5MPa, and a rate of 0.5C to obtain a battery.

[0141] Example 6

[0142] The preparation method of the battery provided in this embodiment is as follows:

[0143] 1) Preparation of positive electrode

[0144] Lithium iron phosphate, binder polyvinylidene fluoride, conductive agent carbon nanotubes and conductive agent SP are mixed in a weight ratio of 96.5:2:0.5:1, N-methylpyrrolidone is added, and the mixture is stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is coated on both sides of an aluminum foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a positive electrode sheet.

[0145] 2) Preparation of negative electrode sheet

[0146] The negative electrode active material graphite, the negative electrode active material silicon carbon, the binder PAA, the binder SBR, the conductive agent CNT and the conductive agent SP are mixed in a weight ratio of 80:10:3:3:2:2, deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 35%; the negative electrode slurry is coated on both sides of the copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0147] 3) Preparation of electrolyte precursor solution

[0148] 4% trimethylolpropane triacrylate, 1% dipentaerythritol hexaacrylate, 0.05% benzoyl peroxide, 25% propylene carbonate (PC), 15% ethylene carbonate (EC), 15% diethyl carbonate (DEC), 25% methyl ethyl carbonate (EMC), 12.05% fluoroethylene carbonate (FEC), and 2.9% vinylene carbonate (VC) are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide (8.5:1) are added to the transparent liquid and dissolved to obtain an electrolyte precursor solution with a lithium salt concentration of 1.45 mol / L.

[0149] 4) Battery assembly

[0150] The positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and assembled to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor solution is added, and a battery is prepared after packaging, pretreatment, curing and formation, and other processes;

[0151] The pretreatment includes: performing a prepolymerization reaction at a temperature of 60°C for 1.5 hours; subsequently, charging the pretreated battery to 3.7V at a temperature of 80°C, a pressure of 2MPa, and a rate of 0.2C; and charging the cured battery to a cutoff voltage of 4.1V at a temperature of 90°C, a pressure of 0.1MPa, and a rate of 0.5C to obtain a battery.

[0152] Example 7

[0153] The preparation method of the battery provided in this embodiment is as follows:

[0154] 1) Preparation of positive electrode

[0155] Lithium manganese iron phosphate, binder polyvinylidene fluoride, conductive agent carbon nanotubes and conductive agent SP are mixed in a weight ratio of 96.5:2:0.5:1, N-methylpyrrolidone is added, and the mixture is stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is coated on both sides of an aluminum foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a positive electrode sheet.

[0156] 2) Preparation of negative electrode sheet

[0157] The negative electrode active material graphite, the negative electrode active material silicon carbon, the binder PAA, the binder SBR, the conductive agent CNT and the conductive agent SP are mixed in a weight ratio of 80:10:3:3:2:2, deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 35%; the negative electrode slurry is coated on both sides of the copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0158] 3) Preparation of electrolyte precursor solution

[0159] 4% pentaerythritol triacrylate, 3% diethylene glycol dimethacrylate, 0.07% benzoyl peroxide, 25% propylene carbonate (PC), 15% ethylene carbonate (EC), 15% diethyl carbonate (DEC), 24% methyl ethyl carbonate (EMC), 11.03% fluoroethylene carbonate (FEC), and 2.9% vinylene carbonate (VC) are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium difluorophosphate (9.5:1) are added to the transparent liquid and dissolved to obtain an electrolyte precursor solution with a lithium salt concentration of 1.45 mol / L.

[0160] 4) Battery assembly

[0161] The positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and assembled to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor solution is added, and a battery is prepared after packaging, pretreatment, curing and formation, and other processes;

[0162] The pretreatment includes: performing a prepolymerization reaction at a temperature of 55°C for 2 hours; then, charging the pretreated battery to 3.7V at a temperature of 80°C, a pressure of 2MPa, and a rate of 0.15C; and charging the cured battery to a cutoff voltage of 4.1V at a temperature of 90°C, a pressure of 0.2MPa, and a rate of 0.5C to obtain a battery.

[0163] Example 8

[0164] The preparation method of the battery provided in this embodiment is as follows:

[0165] 1) Preparation of positive electrode

[0166] Lithium nickel cobalt manganese oxide (nickel cobalt manganese 6:2:2), binder polyvinylidene fluoride, conductive agent carbon nanotubes and conductive agent SP are mixed in a weight ratio of 96.5:2:0.5:1, N-methylpyrrolidone is added, and the mixture is stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is coated on both sides of an aluminum foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a positive electrode sheet.

[0167] 2) Preparation of negative electrode sheet

[0168] The negative electrode active material graphite, the negative electrode active material silicon carbon, the binder PAA, the binder SBR, the conductive agent CNT and the conductive agent SP are mixed in a weight ratio of 85:5:3:3:2:2, deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 35%; the negative electrode slurry is coated on both sides of the copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0169] 3) Preparation of electrolyte precursor solution

[0170] 1% trimethylolpropane trimethacrylate, 3% ethylene glycol dimethacrylate, 5% triethylene glycol dimethacrylate, 0.09% tert-butyl perbenzoate, 25% propylene carbonate (PC), 15% ethylene carbonate (EC), 15% diethyl carbonate (DEC), 25% methyl ethyl carbonate (EMC), 12.05% fluoroethylene carbonate (FEC), and 2.9% vinylene carbonate (VC) are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bis(fluorobis(oxaloyl)phosphate) (7.8:1) are added to the transparent liquid and dissolved to obtain an electrolyte precursor solution with a lithium salt concentration of 1.45 mol / L.

[0171] 4) Battery assembly

[0172] The positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and assembled to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor solution is added, and a battery is prepared after packaging, pretreatment, curing and formation, and other processes;

[0173] The pretreatment includes: performing a prepolymerization reaction at a temperature of 60°C for 1 hour; then, charging the pretreated battery to 3.7V at a temperature of 80°C and a pressure of 1.5MPa; and charging the cured battery to a cutoff voltage of 4.25V at a temperature of 90°C, a pressure of 0.2MPa, and a rate of 0.5C to obtain a battery.

[0174] Comparative Example 1

[0175] The battery provided in this comparative example is a liquid electrolyte, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte. The positive electrode sheet and the negative electrode sheet refer to Example 1, and the electrolyte comprises 26.33% propylene carbonate (PC), 15.8% ethylene carbonate (EC), 15.8% diethyl carbonate (DEC), 26.33% methyl ethyl carbonate (EMC), 12.69% fluoroethylene carbonate (FEC), and 3.05% vinylene carbonate (VC). They are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bistrifluoromethylsulfonyl imide (7:1) are added to the transparent liquid and dissolved to obtain an electrolyte with a lithium salt concentration of 1.45 mol / L.

[0176] Comparative Example 2

[0177] The battery provided in this embodiment can be referred to in Example 3, with the difference being the curing and formation stages. The pretreatment comprises: charging the pretreated battery to 3.7V at 60°C and 3MPa; and charging the cured and formed battery to a cutoff voltage of 4.25V at 80°C, 0.1MPa, and a rate of 0.5C, to obtain a battery.

[0178] Comparative Example 3

[0179] The battery provided in this embodiment can be referred to in Example 3, with the difference being the curing and formation stages. The pretreatment comprises: conducting a prepolymerization reaction at 40°C for 2 hours; subsequently, charging the pretreated battery to 3.7V at 0.5C under a temperature of 40°C and a pressure of 3MPa; and charging the cured and formed battery to a cutoff voltage of 4.25V at a temperature of 40°C, a pressure of 0.1MPa, and a rate of 2C to obtain a battery.

[0180] Test example

[0181] 1. Thermogravimetric analysis

[0182] The batteries provided in Examples 1 to 8 and Comparative Examples 1 to 3 were disassembled to obtain electrolytes. The electrolytes were washed with deionized water, the solidified components were collected, and after drying at 100°C for 24 hours, the solid matter was taken for thermogravimetric testing. When the initial temperature was 25°C, the mass M0 of the electrolyte was tested. Subsequently, the temperature was increased at a heating rate of 5°C / min, and the mass M of the electrolyte was tested at different temperature nodes, with the highest temperature being 600°C. Thermogravimetric mass retention rate = 100% * (M / M0), with temperature as the horizontal axis and mass retention rate as the vertical axis, a thermogravimetric analysis curve was drawn. The thermogravimetric analysis curves of the electrolytes provided in Examples 1 and 4 to 5 are shown in Figures 1-3, respectively. The thermogravimetric data of the electrolytes provided in Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 1.

[0183] Table 1

[0184] 2. XRD test

[0185] After disassembling the batteries of Examples 1 to 8, the electrolytes were subjected to XRD testing at a test angle of 10° to 90°. Based on the test results, the diffraction peaks and their half-peak widths appearing in the X-ray diffraction patterns of the electrolytes of Examples 1 to 8 are listed below.

[0186] Table 2

[0187] 3. Furnace temperature test conditions

[0188] The batteries provided in Examples 1-8 and Comparative Examples 1-3 were discharged to the lower voltage limit at 25°C±5°C and 0.2C, allowed to stand for 10 min, and then charged to the upper voltage limit at 0.5C, with the temperature cut off at 0.05C. The batteries were allowed to stand for 10 min, and the voltage of the fully charged batteries was tested. The batteries were placed in a thermal shock test chamber and the temperature was raised to 200°C at a rate of 5°C±2°C / min. The battery temperature was monitored at different times. The furnace temperature test diagrams of the batteries provided in Examples 1-3 and Comparative Examples 1-2 are shown in Figures 4-8, respectively. The test results of Examples 1-8 and Comparative Examples 1-3 are shown in Table 3.

[0189] Table 3

[0190] 4. Battery cycle test conditions

[0191] The batteries provided in Examples 1 to 8 and Comparative Examples 1 to 3 were discharged at 25°C and 0.2C to the lower limit voltage, left to stand for 10 minutes, and then charged and discharged at 0.5C to the upper limit voltage, with a cut-off of 0.05C. The capacity retention rate information of the battery was collected after 1000 cycles. The initial cycle capacity is A0, the battery is cycled X times, and the test capacity is A x , the battery capacity retention rate is 100% after X cycles*(A x / A0), the test results are shown in Table 4.

[0192] Table 4

[0193] According to the data provided in Tables 1 to 4, the electrolyte provided in the present application has good thermal stability, can effectively prolong the ARC thermal runaway time of the battery, improve the safety of the battery, and improve the cycle performance of the battery.

[0194] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A battery, wherein: including electrolytes; In a nitrogen atmosphere, a thermogravimetric analysis is performed on the electrolyte at a heating rate of 5° C. / min, and the electrolyte has at least one weight loss peak between 100° C. and 600° C.

2. The battery according to claim 1, wherein The weight loss rate of the electrolyte at 100° C. to 600° C. is 3 to 85%.

3. The battery according to any one of claims 1 to 2, wherein: In a nitrogen atmosphere, starting from an initial temperature T0, a thermogravimetric analysis of the electrolyte is performed at a heating rate of 5°C / min, the initial temperature T0 is 25°C, and the mass of the electrolyte at the initial temperature T0 is M0; The electrolyte satisfies at least one of the following: (1) When the temperature T reaches 100°C, the mass of the electrolyte is ≥96.13%*M0; (2) When the temperature T reaches 200°C, the mass of the electrolyte is ≥49.46%*M0; (3) When the temperature T reaches 300°C, the mass of the electrolyte is ≥35.02%*M0; (4) When the temperature T reaches 400°C, the mass of the electrolyte is ≥27.51%*M0; (5) When the temperature T reaches 500°C, the mass of the electrolyte is ≥19.06%*M0; (6) When the temperature T reaches 590°C, the mass of the electrolyte is ≥17.74%*M0.

4. The battery according to any one of claims 1 to 3, wherein The electrolyte has M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y in an X-ray diffraction pattern, M≥1, N≥1; Among them, 10°≤x≤30°, 30°≤y≤50°; The sum of the half-peak widths of the M first diffraction peaks is a, and the sum of the half-peak widths of the N second diffraction peaks is b, wherein 1.2≤b / a≤3.

0.

5. The battery according to claim 4, wherein 1.7≤b / a≤2.2; Or, 2.7≤b / a≤2.

95.

6. The battery according to claim 4, wherein 0.8≤a≤1.4, 1.2≤b≤3.

5.

7. The battery according to any one of claims 1 to 6, wherein The battery is a solid-state battery or a semi-solid-state battery.

8. The battery according to any one of claims 1 to 6, wherein The electrolyte is a solid electrolyte or a semi-solid electrolyte.

9. The battery according to any one of claims 1 to 8, wherein The electrolyte includes a polymer obtained by polymerizing a polymerized monomer, wherein the polymerized monomer includes a functional group, and the functional group includes at least two acrylate groups.

10. The battery according to claim 9, wherein The polymerizable monomers include one or more of bifunctional monomers, trifunctional monomers, tetrafunctional monomers, and hexafunctional monomers.

11. The battery according to claim 10, wherein The bifunctional monomer includes one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, and ethoxylated bisphenol A diacrylate and its derivatives; And / or, the trifunctional monomer includes one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives; and / or, the tetrafunctional monomer comprises ethoxylated (5) pentaerythritol tetraacrylate and its derivatives; And / or, the hexafunctional monomer includes dipentaerythritol hexaacrylate and its derivatives.

12. The battery according to any one of claims 1 to 11, wherein The battery is prepared by a method comprising the following steps: The battery is obtained by sequentially subjecting a battery including an electrolyte precursor solution to pretreatment, curing and formation treatment, and formation treatment, wherein the electrolyte precursor solution includes a polymerizable monomer; Wherein, the pretreatment comprises: subjecting the electrolyte precursor solution including the polymerizable monomer to a prepolymerization reaction at 40° C. to 60° C. for 0.5 h to 2 h; The curing treatment comprises: charging the pretreated battery to 3.7V at a temperature of 60°C to 80°C, a pressure of ≤3MPa, and a rate of ≤0.3C; The chemical formation treatment comprises: charging the battery after the curing chemical formation treatment to a cut-off voltage of ≥4.0V at a temperature of 60°C to 90°C, a pressure of ≤3MPa, and a rate of ≤1C to obtain the battery.

13. The battery according to any one of claims 1 to 12, wherein: The electrolyte includes 0.05 wt % to 9 wt % of a polymer and 91 wt % to 99.5 wt % of an electrolyte.

14. The battery according to claim 13, wherein The electrolyte includes a lithium salt and a non-aqueous organic solvent.

15. The battery according to claim 14, wherein The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide and lithium bistrifluoromethylsulfonyl imide.

16. The battery according to claim 14, wherein The non-aqueous organic solvent is selected from one or more of cyclic carbonates, linear carbonates, and linear carboxylates.

17. The battery according to any one of claims 1 to 16, wherein: It also includes a positive electrode sheet; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material, lithium nickel cobalt oxide, lithium nickel titanium magnesium oxide, lithium nickel oxide, spinel lithium manganese oxide, nickel cobalt tungsten, lithium nickel manganese oxide, and sodium-containing lithium cobalt oxide.

18. The battery according to any one of claims 1 to 17, wherein: It also includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of silicon, silicon carbon, SiOx, lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerenes, graphene, coke, carbon fiber, boron and its derivatives, aluminum and its derivatives, magnesium and its derivatives, bismuth and its derivatives, nickel and its derivatives, silver and its derivatives, zinc and its derivatives, titanium and its derivatives, gallium and its derivatives, indium and its derivatives, tin and its derivatives, lithium nitride, and copper nitride.

19. An electronic device, wherein: A battery comprising any one of claims 1 to 18.